2019
DOI: 10.1002/cphc.201900544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Random Defects Generated on the Surface of Pt(111) on the Electro‐oxidation of Ethanol: An Electrochemical Study

Abstract: In the present work, the Pt(111) surface was disordered by controlling the density of {110}‐ and {100}‐type defects. The cyclic voltammogram (CV) of a disordered surface in acid media consists of three contributions within the hydrogen adsorption/desorption region: one from the well‐ordered Pt(111) symmetry and the other two transformed from the {111}‐symmetry with contributions of {110}‐ and {100}‐type surface defects. The ethanol oxidation reaction (EOR) was studied on these disordered surfaces. Electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 54 publications
(157 reference statements)
5
34
0
Order By: Relevance
“…These results are very similar to previously published data , and the main characteristics observed along the sequence, Pt(111), Pt(776), Pt(554), Pt(775), Pt(332), and Pt(110), are the decrease in the (111) domains, that is, the featureless structure between ∼0.05 and 0.30 V, and the increase of the peak corresponding to the (110) sites near the terrace borders at 0.13 V. Within the hydrogen adsorption region, that is, between 0.06 and 0.35 V, the sharp peak at 0.13 V corresponds to hydrogen adsorption on the 110 step sites overlaid to the hydrogen adsorption on the terrace sites, both adsorption processes give a broad and featureless signal between 0.06 and 0.35 V. In the (bi)­sulfate region, between 0.35 and 0.8 V, the signal reflects the adsorption of the anion on the terrace sites . Also, a small {100} defects formation cannot be discarded for stepped surfaces, once a contribution at 0.28 V assigned to this face is clearly seen, it is more pronounced for Pt(111) and Pt(776) surfaces, while for the others ones they are practically unobserved …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are very similar to previously published data , and the main characteristics observed along the sequence, Pt(111), Pt(776), Pt(554), Pt(775), Pt(332), and Pt(110), are the decrease in the (111) domains, that is, the featureless structure between ∼0.05 and 0.30 V, and the increase of the peak corresponding to the (110) sites near the terrace borders at 0.13 V. Within the hydrogen adsorption region, that is, between 0.06 and 0.35 V, the sharp peak at 0.13 V corresponds to hydrogen adsorption on the 110 step sites overlaid to the hydrogen adsorption on the terrace sites, both adsorption processes give a broad and featureless signal between 0.06 and 0.35 V. In the (bi)­sulfate region, between 0.35 and 0.8 V, the signal reflects the adsorption of the anion on the terrace sites . Also, a small {100} defects formation cannot be discarded for stepped surfaces, once a contribution at 0.28 V assigned to this face is clearly seen, it is more pronounced for Pt(111) and Pt(776) surfaces, while for the others ones they are practically unobserved …”
Section: Resultssupporting
confidence: 92%
“…The hysteresis has been associated with the formation of strongly adsorbed species, mainly CO, that are formed on the electrode surface at low potentials, during the positive-going scan, and to the oxidation of solution species in the nonpoisoned surface along the reverse sweep . Similar hysteresis has been observed in the oxidation of several organic molecules. , …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Concerning the importance of the steps/defects on the surfaces, it is well documented that the electro-oxidation of CO is a surface structure sensitive reaction, in which (crystalline 9 and/or random [10][11][12] ) defects on the surface are a beneficial ingredient for achieving high catalytic activities at low overpotentials [9][10][11] . Studies using stepped Pt surfaces consisting of different width (111) terraces interrupted by (110) monoatomic steps have shown that the CO electro-oxidation reaction rate increases with increasing steps density, and that extrapolation of the reaction rate to a surface with zero defect density, equivalent to a perfect Pt(111) surface, closely corresponds to a negligible reaction rate 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there was no ordinary CO pre-oxidation for the CO layer formed at 0.100 V, because the non-adsorbed CO was completely eliminated from the solution.Figure 3Bshows the corresponding cyclic voltammograms for the bead-type poly-oriented Pt electrode in 0.1 M HClO4 solution. The pair of small peaks appearing at ~0.80 V could have the same relationships with the feature appearing at ~0.80 V in the voltammograms for the Pt(111) electrode in perchloric acid solutions.As stated above, to provide evidence that, at least, traces of CO in the solution phase are required for the appearance of the CO pre-oxidation in voltammograms for CO stripping employing stepped Pt surfaces, experiments were performed using the Pt(332) electrode after dosing with CO at 0.100 V for 5 minutes, with the application of different CO elimination times(30,12,8, and 5 minutes). The results are shown inFigure 5.…”
mentioning
confidence: 99%